Device and method for testing electrochemical corrosion performance of metal magnetic powder
By adsorbing metallic magnetic powder onto the surface of a magnet to test its electrochemical corrosion performance, the problems of complex testing and result interference in existing technologies are solved, and a more direct and accurate evaluation of electrochemical corrosion performance is achieved.
Patent Information
- Application Number
- CN202511203095.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-27
- Publication Date
- 2025-10-31
AI Technical Summary
Existing methods for testing the electrochemical corrosion performance of metal magnetic powders are complex and the test results are affected by the bonding substrate, making it difficult to directly reflect the intrinsic electrochemical corrosion performance of metal magnetic powders.
Metal magnetic powder is adsorbed onto the surface of a magnet as a working electrode, and electrochemical corrosion performance is tested using a three-electrode system. This avoids the use of a bonding substrate and directly reflects the corrosion resistance of the metal magnetic powder in a corrosive environment.
The testing process has been simplified, and the test results are more realistic and accurate. It can characterize the surface coating modification state of metal magnetic powder and reflect its electrochemical corrosion resistance in corrosive environments.
Smart Images

Figure CN120869958A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of material corrosion and protection technology, and more specifically, relates to a device and method for testing the electrochemical corrosion performance of metal magnetic powder. Background Technology
[0002] Metallic magnetic powders have wide applications in electronics, chemical engineering, and materials science due to their high saturation magnetization and high Curie temperature. However, they are susceptible to oxidation and chemical corrosion in their application environments, which alters their composition and structure, thereby affecting their electromagnetic properties. Therefore, testing the electrochemical corrosion performance of metallic magnetic powders is an important method for characterizing their composition, structure, and application performance stability.
[0003] Currently, in the electrochemical corrosion performance testing of metal magnetic powders, since the magnetic powder is in a dispersed state, it needs to be mixed with a binder such as polymer resin or rubber to form a composite coating or block, which is then applied to the surface of the working electrode for electrochemical reaction testing. This method ensures that the metal magnetic powder maintains a stable morphology during testing, but the introduction of the polymer binder and the adjustment of its ratio with the magnetic powder will alter the surface state of the magnetic powder to varying degrees (forming a coating layer), leading to deviations between the intrinsic electrochemical corrosion performance of the metal magnetic powder and the test results. Furthermore, another method for fabricating the working electrode involves mixing the metal magnetic powder with a Nafion solution, utilizing the film-forming properties of the Nafion solution to fix the powder on the surface of a glassy carbon electrode for electrochemical corrosion performance testing. However, the Nafion film also alters the surface state of the metal magnetic powder, affecting its electrochemical reaction behavior with the corrosion solution, making it difficult to directly reflect the intrinsic electrochemical corrosion performance of the metal magnetic powder. Therefore, while existing methods for fabricating metal magnetic powder electrodes can meet the requirements for electrochemical corrosion performance testing to some extent, the metal magnetic powder test electrodes still suffer from drawbacks such as complex fabrication processes and numerous influencing factors on the test results. Therefore, developing a metal magnetic powder working electrode that does not require the introduction of a bonding substrate and its electrochemical corrosion performance testing method is of great practical significance. Summary of the Invention
[0004] In view of the above-mentioned defects or improvement needs of the prior art, the present invention provides a device and method for testing the electrochemical corrosion performance of metal magnetic powder, thereby solving the technical problems of complex testing process and test results being affected by multiphase composite interference in the prior art.
[0005] To achieve the above objectives, according to one aspect of the present invention, a metal magnetic powder electrochemical corrosion performance testing device is provided, comprising an electrolytic cell, a working electrode, a reference electrode, and a counter electrode; the working electrode comprises a magnet and metal magnetic powder; the metal magnetic powder is adsorbed at only one end of the magnet; the electrolytic cell is used to hold a corrosive medium; the end of the magnet with the adsorbed metal magnetic powder is located in the electrolytic cell; one end of the reference electrode and the counter electrode are both located in the electrolytic cell.
[0006] Preferably, the magnet is a columnar magnet; the side of the columnar magnet is coated with resin.
[0007] Preferably, the metal magnetic powder is selected from one or more of reduced iron powder, carbonyl iron powder, iron-cobalt alloy powder, iron-silicon alloy powder, and iron-nickel alloy powder; Preferably, the magnet is selected from samarium cobalt permanent magnet alloy, aluminum nickel cobalt permanent magnet alloy, or iron chromium cobalt permanent magnet alloy.
[0008] Preferably, the corrosive medium is a sodium chloride solution or a hydrochloric acid solution; more preferably, the mass fraction of the solute in the corrosive medium is 3% to 10%.
[0009] Preferably, the resin is selected from epoxy resin or vinyl resin.
[0010] Preferably, the reference electrode is a silver and silver chloride electrode; the counter electrode is a platinum sheet electrode.
[0011] According to another aspect of the present invention, a method for testing the electrochemical corrosion performance of metal magnetic powder is provided, comprising the following steps: (1) Adsorb metal magnetic powder at one end of the magnet and use the magnet with adsorbed metal magnetic powder as the working electrode; (2) Add a corrosive medium to the electrolytic cell and insert the end of the magnet with the metal magnetic powder adsorbed into the corrosive medium; (3) Insert one end of the reference electrode and the counter electrode into the corrosive medium; connect the working electrode, the reference electrode and the counter electrode without being inserted into the corrosive medium to an external circuit to perform electrochemical corrosion performance testing of the metal magnetic powder.
[0012] Preferably, the electrochemical corrosion performance test includes one or more of the following: corrosion potential test, AC impedance test, constant potential polarization test, and cyclic potentiodynamic polarization test.
[0013] In summary, compared with the prior art, the above-described technical solutions conceived by this invention can achieve the following beneficial effects: 1. This invention obtains a fixed shape by adsorbing metal magnetic powder onto the surface of a magnet, without the need to form a test electrode with a bonding substrate. This method can more directly reflect the corrosion resistance of metal magnetic powder in a corrosive environment and avoids interference with the test results caused by the bonding substrate.
[0014] 2. The method for testing the electrochemical corrosion performance of metal magnetic powder proposed in this invention disperses and adsorbs metal magnetic powder on the surface of a magnet, and then connects the magnet to the working electrode to perform the test. This method has the characteristics of simple operation process.
[0015] 3. The test method for the electrochemical corrosion performance of metal magnetic powder proposed in this invention can be used to characterize the surface coating modification state of metal magnetic powder. By changing the electrochemical corrosion performance indicators such as corrosion potential and AC impedance, the integrity and density of the surface coating modification layer of metal magnetic powder can be indirectly reflected, which has important engineering application value. Attached Figure Description
[0016] Figure 1 This is a schematic diagram of the three-electrode structure (counter electrode, reference electrode, and working electrode) of the present invention; Figure 2 The results are the electrochemical test results of reduced iron powder (Fe) and its alumina-coated powder (Fe@Al2O3) under this test method in Example 1 of the present invention; where a is the open circuit potential (OCP)-time curve; b is the Tafel curve; c is the impedance modulus-frequency Bode plot; and d is the Nyquist plot.
[0017] Figure 3 The results of the electrochemical tests of carbonyl iron powder (CIP) and its alumina-coated powder (CIP@Al2O3) in Example 2 of this invention under this test method are shown in the figure; where a is the open circuit potential (OCP)-time curve; b is the Tafel curve; c is the impedance modulus-frequency Bode plot; and d is the Nyquist plot.
[0018] Figure 4 The results are as follows: Example 3 of the present invention: the electrochemical test results of the iron-cobalt alloy powder (Fe-Co) and its alumina-coated powder (Fe-Co@Al2O3) under this test method; where a is the open circuit potential (OCP)-time curve; b is the Tafel curve; c is the impedance modulus-frequency Bode plot; and d is the Nyquist plot. Detailed Implementation
[0019] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.
[0020] Example 1 This embodiment provides a method for testing the electrochemical corrosion performance of reduced iron powder (Fe) and alumina-coated iron powder (Fe@Al2O3), which includes the following steps: (1) Weigh 0.1 g of Fe and Fe@Al2O3 powder respectively. Select AlNiCo magnet as adsorption carrier. The magnet is cylindrical with a diameter of 8 mm and a height of 40 mm. Select 3.5% sodium chloride solution (salt spray environment) as corrosion medium. Use an electrolytic cell with a volume of 200 ml, an inner diameter of 65 mm, an outer diameter of 70 mm and a height of 70 mm. There are three electrode holes on the cover of the electrolytic cell, two with a diameter of 6.5 mm and one with a diameter of 8 mm. Use an electrochemical workstation. The reference electrode in the three electrodes is a silver / silver chloride electrode and the counter electrode is a platinum sheet electrode.
[0021] (2) A layer of polymer resin is coated on the side of the AlNiCo magnet with a coating height of 20 mm and a coating thickness of 2 mm to isolate the corrosive medium. The uncoated part is directly connected to the working electrode. The metal magnetic powder is uniformly adsorbed on the magnet surface to ensure that the metal magnetic powder is tightly bonded to the magnet surface.
[0022] (3) Connect the magnets adsorbed with Fe and Fe@Al2O3 powder to the working electrode to form a conductive path; place the magnets in the electrolytic cell and add 3.5% sodium chloride solution; insert the magnets, reference electrode and counter electrode into the electrode holes of the electrolytic cell cover plate to ensure good contact between the electrodes and the solution.
[0023] (4) Set the test parameters on the electrochemical workstation and perform electrochemical tests. The open circuit potential (OCP) test time is 1200 s, and the AC impedance is set to a frequency (10 Hz). 5 -10 -2 (Hz), the set AC amplitude is 10 mV relative to open circuit, the set AC amplitude for potentiodynamic scanning is 0.3 V relative to open circuit, and the scan rate is 1 mV / s.
[0024] Example 2 This embodiment provides a method for testing the electrochemical corrosion performance of carbonyl iron powder (CIP) and alumina-coated carbonyl iron powder (CIP@Al2O3), which includes the following steps: (1) Weigh 0.05 g of CIP and CIP@Al2O3 powder respectively. Select AlNiCo magnet as adsorption carrier. The magnet is cylindrical with a diameter of 8 mm and a height of 40 mm. Select 3.5% sodium chloride solution (salt spray environment) as corrosion medium. Use an electrolytic cell with a volume of 200 ml, an inner diameter of 65 mm, an outer diameter of 70 mm and a height of 70 mm. There are three electrode holes on the cover of the electrolytic cell, two with a diameter of 6.5 mm and one with a diameter of 8 mm. Use an electrochemical workstation. The reference electrode in the three electrodes is a silver / silver chloride electrode and the counter electrode is a platinum sheet electrode.
[0025] (2) A layer of polymer resin is coated on the side of the AlNiCo magnet with a coating height of 20 mm and a coating thickness of 2 mm to isolate the corrosive medium. The uncoated part is directly connected to the working electrode. The metal magnetic powder is uniformly adsorbed on the magnet surface to ensure that the metal magnetic powder is tightly bonded to the magnet surface.
[0026] (3) Connect the magnets adsorbed with CIP and CIP@Al2O3 powder to the working electrode to form a conductive path; place the magnets in the electrolytic cell and add 3.5% sodium chloride solution; insert the magnets, reference electrode and counter electrode into the electrode holes of the electrolytic cell cover plate to ensure good contact between the electrodes and the solution.
[0027] (4) Set the test parameters on the electrochemical workstation and perform electrochemical tests. The open circuit potential (OCP) test time is 1200 s, and the AC impedance is set to a frequency (10 Hz). 5 -10 -2 (Hz), the set AC amplitude is 10 mV relative to open circuit, the set AC amplitude for potentiodynamic scanning is 0.3 V relative to open circuit, and the scan rate is 1 mV / s.
[0028] Example 3 This embodiment provides a method for testing the electrochemical corrosion performance of iron-cobalt alloy powder (Fe-Co) and alumina-coated iron-cobalt alloy powder (Fe-Co@Al2O3), which includes the following steps: (1) Weigh 0.025 g of Fe-Co and Fe-Co@Al2O3 powder respectively. Select AlNiCo magnet as adsorption carrier. The magnet is cylindrical with a diameter of 8 mm and a height of 40 mm. Select 3.5% sodium chloride solution (salt spray environment) as corrosion medium. Use an electrolytic cell with a volume of 200 ml, an inner diameter of 65 mm, an outer diameter of 70 mm and a height of 70 mm. There are three electrode holes on the cover of the electrolytic cell, two with a diameter of 6.5 mm and one with a diameter of 8 mm. Use an electrochemical workstation. The reference electrode in the three electrodes is a silver / silver chloride electrode and the counter electrode is a platinum sheet electrode.
[0029] (2) A layer of polymer resin is coated on the side of the AlNiCo magnet with a coating height of 20 mm and a coating thickness of 2 mm to isolate the corrosive medium. The uncoated part is directly connected to the working electrode. The metal magnetic powder is uniformly adsorbed on the magnet surface to ensure that the metal magnetic powder is tightly bonded to the magnet surface.
[0030] (3) Connect the magnets adsorbed with Fe-Co and Fe-Co@Al2O3 to the working electrode to form a conductive path; place the magnet in the electrolytic cell and add 3.5% sodium chloride solution; insert the magnet, reference electrode and counter electrode into the electrode holes of the electrolytic cell cover plate to ensure good contact between the electrode and the solution.
[0031] (4) Set the test parameters on the electrochemical workstation and perform electrochemical tests. The open circuit potential (OCP) test time is 1200 s, and the AC impedance is set to a frequency (10 Hz). 5 -10 -2 (Hz), the set AC amplitude is 10 mV relative to open circuit, the set AC amplitude for potentiodynamic scanning is 0.3 V relative to open circuit, and the scan rate is 1 mV / s.
[0032] A schematic diagram of the three-electrode structure (counter electrode, reference electrode, and working electrode) of the present invention is shown below. Figure 1 As shown, the electrochemical test results (open circuit potential, Tafel polarization curve, impedance modulus, and real and imaginary parts of impedance) for Examples 1, 2, and 3 are presented. The test end of the magnet working electrode adsorbs metallic magnetic powder, which comes into contact with the reaction solution during testing and undergoes an electrochemical reaction. This allows for the acquisition of the intrinsic properties of the metallic magnetic powder, avoiding the influence of the coating effect of the bonding substrate on the powder surface state in traditional methods. Therefore, the test results are more realistic and accurate.
[0033] Open-circuit potential and corrosion potential reflect a material's corrosion tendency and stability, corrosion current density quantitatively assesses the corrosion rate, and impedance modulus reflects corrosion resistance. These parameters collectively provide important basis for comprehensively evaluating a material's corrosion resistance. Generally, the more positive the open-circuit potential, the more positive the corrosion potential, the lower the corrosion current density, and the larger the impedance modulus, the better the corrosion resistance. Figure 2-3 As can be seen from the results in Tables 1-3, the examples clearly compare the differences in electrochemical corrosion performance between the metal magnetic powder and its coated magnetic powder, demonstrating the excellent testing effect of this invention. This invention not only has a simple operating procedure but also more realistically reflects the electrochemical corrosion resistance of metal magnetic powder in corrosive environments, avoiding interference introduced by the bonding substrate in traditional methods.
[0034] Table 1 shows the relevant results of electrochemical tests on Fe and Fe@Al2O3.
[0035] Table 2 shows the relevant results of electrochemical tests on CIP and CIP@Al2O3.
[0036] Table 3 shows the relevant results of electrochemical tests on Fe-Co and Fe-Co@Al2O3.
[0037] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A device for testing the electrochemical corrosion performance of metal magnetic powder, characterized in that, It includes an electrolytic cell, a working electrode, a reference electrode, and a counter electrode; the working electrode includes a magnet and metal magnetic powder; the magnet has the metal magnetic powder adsorbed at only one end; the electrolytic cell is used to hold a corrosive medium; the end of the magnet with the metal magnetic powder adsorbed is located in the electrolytic cell; one end of the reference electrode and the counter electrode are both located in the electrolytic cell.
2. The metal magnetic powder electrochemical corrosion performance testing device as described in claim 1, characterized in that, The magnet is a columnar magnet; the side of the columnar magnet is coated with resin.
3. The metal magnetic powder electrochemical corrosion performance testing device as described in claim 1 or 2, characterized in that, The metal magnetic powder is selected from one or more of reduced iron powder, carbonyl iron powder, iron-cobalt alloy powder, iron-silicon alloy powder, and iron-nickel alloy powder.
4. The metal magnetic powder electrochemical corrosion performance testing device as described in claim 1, characterized in that, The magnet is selected from samarium cobalt permanent magnet alloy, aluminum nickel cobalt permanent magnet alloy, or iron chromium cobalt permanent magnet alloy.
5. The metal magnetic powder electrochemical corrosion performance testing device as described in claim 1, characterized in that, The corrosive medium is a sodium chloride solution or a hydrochloric acid solution; preferably, the mass fraction of the solute in the corrosive medium is 3% to 10%.
6. The metal magnetic powder electrochemical corrosion performance testing device as described in claim 2, characterized in that, The resin is selected from epoxy resin or vinyl resin.
7. The metal magnetic powder electrochemical corrosion performance testing device as described in claim 1, characterized in that, The reference electrode is a silver and silver chloride electrode; the counter electrode is a platinum sheet electrode.
8. A method for testing the electrochemical corrosion performance of metal magnetic powder, characterized in that, Includes the following steps: (1) Adsorb metal magnetic powder at one end of the magnet and use the magnet with adsorbed metal magnetic powder as the working electrode; (2) Add a corrosive medium to the electrolytic cell and insert the end of the magnet with the metal magnetic powder adsorbed into the corrosive medium; (3) Insert one end of the reference electrode and the counter electrode into the corrosive medium; connect the working electrode, the reference electrode and the counter electrode without being inserted into the corrosive medium to an external circuit to perform electrochemical corrosion performance testing of the metal magnetic powder.
9. The method for testing the electrochemical corrosion performance of metal magnetic powder as described in claim 8, characterized in that, The electrochemical corrosion performance test is selected from one or more of the following: corrosion potential test, AC impedance test, constant potential polarization test, and cyclic potentiodynamic polarization test.
Citation Information
Patent Citations
Magnetic core powder spraying film-forming agent and application method thereof
CN110918979A
Magnetic working electrode
CN201622261U
Coating corrosion monitoring probe
CN206479439U
Apparatus for electrochemical analysis
SU1762213A1
Magnetic powder and magnet
US20200070241A1